A review on teacher training's drawbacks, barriers and challenges: Conventional to digital technology transition - R. M. Rasli; N. A. M. Zulkefli; N. A. A. Azizir; F. M. Razali; S. A. Salim; N. M. Norwawi; Nurlida Basir (University of El Oued, 2024)
Education either formal or informal plays an important role to help the masses to acquire the necessary knowledge and skills. Teachers training programs have to be periodically reviewed and revamped (if necessary) to help produce competent teachers who are excellent in content, pedagogical and technological knowledge. Studies shown that such training is lacking due to several barriers (administration, organization, communication and self-related), drawbacks and challenges which are faced by pre-service teachers in their teaching practice during practicum in actual classrooms. It also elaborates the various importance technologies notably Web 2.0 that can be implemented to help improve the current teaching practice in coping with the teaching demands in the classroom. With proper technology integration, learning can take place more efficiently and effectively, ultimately lead to better nation building.